Modelled decomposition kinetics of flame retarded poly(vinyl acetate). (August 2016) - Rimez, B.; Van Assche, G.; Bourbigot, S.; Rahier, H.
Abstract: Previously determined degradation mechanisms of a model polymer compound, poly(vinyl acetate) (PVAc), blended with two different flame retardants, ammonium poly(phosphate) (APP) and melamine isocyanurate (MIC), were used for reaction rate parameter optimization using a kinetic modelling and simulation software. Rate parameters for all different decomposition reactions were established for inert and oxidative conditions, giving insight into all interactions between flame retardants and polymer. Analyzing kinetic data, it was found that APP catalyzes the deacetylation reaction of PVAc, independent from the mixing ratio, and has a higher catalyzing effect than oxygen. Down to ten parts APP per one hundred parts of PVAc, APP is also a very efficient crosslinker with PVAc upon decomposition. MIC on the other hand acts in two ways: as heat-sink flame retardant during deacetylation and charring of the polymer, whereas during this charring step, another part of MIC crosslinks with PVAc. Simulations using kinetic parameter sets of PVAc/MIC and PVAc/APP blends showed that MIC and APP interact independently with PVAc when both flame retardants are mixed together into PVAc. A very efficient flame retarded composite is as such obtained at low loading levels.